High spin states in 74Br - García Bermúdez, G. J.; Filevich, Alberto; Kreiner, A. J.; Mariscotti, M. A. J.; Baktash, C.; der Mateosian, E.; Thieberger, P. (1981)
Fil: García Bermúdez, G. J. Comisión Nacional de Energía Atómica; Argentina